The Role of Profitability and Liquidity in Meeting the Feasibility Standards of Sharia Banking with Capital Adequacy as A Moderating Variable in Indonesia - Yahya, Padli Pawaid; Setyono, Joko (Department of Economics, Faculty of Economics and Business, Universitas Airlangga, 2024)
This study investigates the impact of profitability and liquidity on bank viability, considering capital adequacy as a moderating factor in Islamic commercial banks in Indonesia. The research sample consists of 9 Islamic commercial banks from 2018 to 2022. The dependent variable, bank survival, is assessed using Return on Assets (ROA). The independent variable, profitability, is measured by Return on Equity (ROE), with Capital Adequacy Ratio (CAR) as the moderating variable. Control variables include Net Profit Margin (NPM), Operational Efficiency (BOPO), and Loan to Deposit Ratio (LDR). Analysis is conducted using multiple linear regression with a Fixed Effects model. The findings indicate that capital adequacy functions as a pure moderator, enhancing the relationship between NPM and ROA while weakening the relationship between ROE and ROA.